Excessive use of social networking sites and financial well-being among working millennials : a parallel-serial mediation model - Long, She; Lan, Ma; Voon, Mung Ling; Agnes Lim, Siang Siew (Emerald Publishing Limited, 2022)
Purpose This study aimed to investigate the mediating role of financial attitude and perceived behavioral control with financial behavior in the association between excessive use of social networking sites (SNSs) and financial well-being among working millennials.